1991
DOI: 10.1073/pnas.88.16.6926
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of plant sterols on water permeability and on acyl chain ordering of soybean phosphatidylcholine bilayers.

Abstract: To gain some insight into the structural and functional roles of sterols in higher plant cells, various plant sterols have been incorporated into soybean phosphatidyicholine (PtdCho) bilayers and tested for their ability to regulate water permeability and acyl chain ordering. Sitosterol was the most efficient sterol in reducing the water permeability of these vesicles and stigmasterol appeared to have no significant effect.Vesicles containing 24fmethylcholesterol exhibited an intermediate behavior, similar to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
150
1

Year Published

1993
1993
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 212 publications
(162 citation statements)
references
References 36 publications
10
150
1
Order By: Relevance
“…For example, Grandmougin-Ferjani et al (1997) revealed that cholesterol and stigmasterol were able to stimulate the Hþ pump of the ATPase in higher plant plasma membranes. Furthermore, stigmasterol was less efficient in regulating membrane permeability than sitosterol and 24-methylcholesterol (Schuler et al, 1991). Both examples suggest that not all of the functions of the various phytosterols have yet been explored.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Grandmougin-Ferjani et al (1997) revealed that cholesterol and stigmasterol were able to stimulate the Hþ pump of the ATPase in higher plant plasma membranes. Furthermore, stigmasterol was less efficient in regulating membrane permeability than sitosterol and 24-methylcholesterol (Schuler et al, 1991). Both examples suggest that not all of the functions of the various phytosterols have yet been explored.…”
Section: Introductionmentioning
confidence: 99%
“…hyd1-1 and hyd1-2 mutants showed no significant differences. Sitosterol and campesterol are the most abundant sterols in Arabidopsis, each being essential in ordering acyl chains in the membrane lipid bilayer and in regulating membrane permeability; stigmasterol cannot functionally replace either sterol (Schuler et al, 1991;Hartmann, 1998). These results demonstrate the requirement for a functional ⌬8-⌬7 sterol isomerase activity for sterol composition in Arabidopsis and indicate that mutations in sterol isomerase (in hyd1) and in C14 reductase (in hyd2/fk), respectively, result in similar gross changes in sterol profiles.…”
Section: Hyd1 and Hyd2 Are Sterol Biosynthetic Mutantsmentioning
confidence: 99%
“…1) is the substrate of the first methylation reaction, resulting in 24-methylene cycloartanol (11) [4-71, whereas 24-methylene lophenol (IV) is the preferred substrate for the second methylation, yielding 24-ethylidene lophenol (V) [8,91 (Fig. 1).…”
mentioning
confidence: 99%